The Enchanting Flora of Chamba: Unveiling Sacred and Magico-Religious Plants in Himachal Pradesh - Rawat, Suman; Kumar, Rajinder (Ethnobotany Research and Applications, 2024)
Background: The current research was carried out in the Chamba district of Himachal Pradesh to investigate and document ethno-magico-religious beliefs based on plant uses. Methods: Data was collected through extensive field surveys using semi-structured questionnaires and open discussions with various ethnic groups. This study involved 45 informants, primarily older individuals with no formal education level. Magico-religious beliefs of plants were categorized into magic beliefs, sacred practices, social ceremonies, and taboos. The data was analysed with the help of quantitative indices such as informant consensus factor (ICF), relative frequency of citation (RFC), relative importance index (RI), cultural value (CV) and cultural importance index (CI). Results: The 45 households, provided the information of 47 plant species belonged to 27 families were documented. Herb and tree worship were common, with 21 and 18 species associated with religious beliefs. The most utilized plant parts were the whole plant, fruits, and leaves. The social ceremonies use category had the highest consensus factor among informants for uniform information. Cynodon dactylon had the highest citation frequency, and Hordeum vulgare ranked highest in cultural importance. Conclusions: Comparisons with previous studies showed the conservation of certain plant species across India based on religious beliefs. This conservation contributes to biodiversity and traditional knowledge conservation. Overall, the study emphasizes the cultural significance of plants and the need for conservation strategies integrating cultural values. Keywords: Sacred, Sustainable, Deities, Relative importance, Cultural value